Model Pengembangan Life Skill pada Perempuan Korban Human Trafficking - Muhammad Tisna Nugraha (Raheema, 2017)
Human trafficking is one of global problems faced by societies in today digital era. The increasing number of victims and criminals, in quality and quantity, has also influenced the number of problems on human rights, social, economics, health, and laws in many countries within the world. Furthermore, human trafficking is a well-organized crime among countries in the world. Indonesia, especially, which has many citizen is also one of targeted country on trafficking crimes. Moreover, there are so many efforts performed to minimize the number of human trafficking in Indonesia. However, most of them are centered on preventive movement after the crime or when the crime is being done, that could not significantly give an effect to the victims after the crime happened. Therefore, the comprehend solution is needed by giving a life-skill training, in order to provide them an ability to create something and being independent in the future.